Effect of using the Matrix Values for NSP-degrading enzymes on performance, water intake, litter moisture and jejunal digesta viscosity of broilers fed barley-based diet - Moftakharzadeh, Seyed Adel; Moravej, Hossein; Shivazad, Mahmud (Acta Scientiarum. Animal Sciences, 2017)
In this study, we have evaluated the effect of three multi-enzymes nutrient matrix values and compared the results with that fed barley and the corn diets without enzyme. In entire period, addition of all enzymes to the barley-based diet significantly (p < 0.05) increased feed intake (FI) and the highest intake was for birds that fed enzyme A (p < 0.05). Overall, from 0 to 42 days, average daily gain (ADG) was significantly (p < 0.05) increased by enzyme and birds fed enzyme A had the highest body weight (p < 0.05). Generally, from 0 to 42 d of age, feed conversion ratio (FCR) was significantly (p < 0.05) improved when enzyme added to barley-based diet, but there were no significant differences among diets containing enzymes A and C and the corn-based diet. The carcass weight, and the relative weight of the abdominal fat were significantly increased by enzyme, while small intestine and cecum decreased with enzyme addition (p < 0.05). Enzyme significantly decreased jejunal viscosity at Day 23 (p < 0.05), whereas pH of jejunal digesta was not changed (p > 0.05). Litter moisture and water to feed ratio at 15, 25, and 33 days of age significantly decreased by addition of all enzymes (p < 0.05). In conclusion, considering nutrient matrix values for all used enzymes improved performance of broilers and can be used in formulating diets commercial broiler diets based on barley.